Longitudinal omics study of transcriptional dynamics in Lactobacillus crispatus - SiLing Ren; Huimin Jiang; Xiaohua Liu; Daju Zhou; Liping Liu; Lan Wang; Yi Lan; Yi Xiao; Liangdan Tang (PLoS ONE, 2026)
Background The vaginal microbiome is an important component of female reproductive health. Community State Type I (CST-I), which is dominated by Lactobacillus crispatus , is generally considered to be closely associated with a healthy vaginal microecological state. Although the taxonomic composition of CST-I communities remains relatively stable, the transcriptional dynamics of Lactobacillus crispatus across different phases of the menstrual cycle remain unclear. Methods A healthy reproductive-age woman with a stable CST-I vaginal microbiome was enrolled in this longitudinal study. Vaginal secretion samples were collected at six non-menstrual time points throughout a menstrual cycle. Third-generation full-length 16S rRNA gene sequencing and metatranscriptomic sequencing were performed. Differential transcript expression analysis, KEGG pathway enrichment analysis, and Mfuzz time-series clustering were applied to systematically characterize the transcriptional dynamics of the vaginal microbiome across different phases. Results Full-length 16S rRNA gene sequencing confirmed that Lactobacillus crispatus remained the dominant species at all six sampling time points, with no substantial changes in overall community composition. However, metatranscriptomic analysis revealed pronounced phase-specific transcriptional reprogramming. During the pre-ovulatory phase, pathways involved in DNA replication, biosynthesis, and central carbon metabolism were upregulated. On the first day after ovulation, pathways associated with carbohydrate utilization, quorum sensing, and redox homeostasis were selectively upregulated. During the mid-to-late luteal phase, pathways related to cell proliferation and growth were generally downregulated, whereas pathways involved in cofactor biosynthesis, the pentose phosphate pathway, and D-amino acid metabolism showed increased expression. Mfuzz clustering further revealed distinct phase-specific functional transitions in L. crispatus that were absent in non- L. crispatus lactobacilli. Conclusion The ecological dominance of Lactobacillus crispatus is maintained not solely through numerical abundance, but also through rhythmic and phase-specific transcriptional regulation. Dynamic functional remodeling and metabolic plasticity may represent important mechanisms underlying its long-term persistence and ecological dominance within healthy CST-I vaginal communities.